Legal Aspects of Inheritance in Multinational Families - Ion, Gabriel Florinel (Acta Universitatis Danubius. Juridica, 2024)
The article addresses the legal complexity of inheritance in the context of multinational families. It examines the legal framework, both nationally and internationally, and highlights the importance of conventions and treaties in this area to harmonize regulations. In the first instance, the challenges posed by conflicts of laws and principles of private international law are discussed, including difficulties related to the choice of applicable law and the recognition of judgments in various jurisdictions. Another central aspect of the paper is the analysis of specific regulations in the European Union, the United States and other regions, highlighting the differences and similarities between them. The rights of heirs, especially those from mixed marriages or civil partnerships, are dealt with in a detailed manner, outlining the legal protection they enjoy. The article explores relevant jurisprudence to illustrate the applicability of legal norms in concrete cases. The conclusions bring to the fore recommendations for improving the legislative framework and future research directions are proposed, in order to adapt the regulations to the increasingly complex realities of multinational families.